2021
DOI: 10.3390/jcm10214923
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lymph Node Count on Oncological Outcome of Radical Cystectomy in Chemotherapy Pre-Treated and Chemotherapy-Naïve Patients with Muscle Invasive Bladder Cancer

Abstract: Radical cystectomy (RC) with pelvic lymph node dissection (PLND) remains the mainstay of treatment for muscle-invasive bladder cancer (MIBC). The extent of PLND and number of removed lymph nodes (LNs) have been associated with improved staging and survival outcomes in several series of RC patients. Neoadjuvant chemotherapy (NAC) has become standard of care for cisplatin-eligible patients qualified to RC, yet few studies on PLND stratified cases according to the receipt of NAC. We aimed to address this issue an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…However, little is known about the therapeutic significance of LND for patients receiving NAC. Lemeninski et al 19 found that the 3-year OS did not improve with more DLNs in patients undergoing NAC (56.3% vs. 54.63%, p = 0.465). However, the number of patients who received NAC was small (n = 83), and a multivariate analysis was not performed.…”
Section: Discussionmentioning
confidence: 98%
“…However, little is known about the therapeutic significance of LND for patients receiving NAC. Lemeninski et al 19 found that the 3-year OS did not improve with more DLNs in patients undergoing NAC (56.3% vs. 54.63%, p = 0.465). However, the number of patients who received NAC was small (n = 83), and a multivariate analysis was not performed.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, a prospective randomized controlled trial showed that extended lymphadenectomy does not have the superiority over limited one with regard to RFS (5-year RFS 65% vs. 59%; HR = 0.84; p = 0.36) and CSS (5-year CSS 76% vs. 65%; HR = 0.70; p = 0.10) (38). Moreover, Leminski et al proved a range of 10-15 LNs to have prognostic significance, while greater numbers of removed nodes resulted in an increase of OS up to 14% (24). According to Koppie et al (25), removing 10 LNs may represent a thorough LN cleanout from a limited LN template, or a relatively incomplete dissection of LNs from an extended LN template, but found no support for a concept of a minimum number of LNs sufficient for optimizing bladder cancer outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…-no Clavien-Dindo grade III-V complications at 90 days and no long-term complications related to UD < 12 months -negative surgical margins (all soft tissue and urethral and ureteral) in post-cystectomy pathological report, ≥10 LN removal during the procedure, and no clinical relapse of bladder cancer ≤12 months after RC found in the follow-up CT. Based on other authors' observations, we included the threshold of 10 LNs in further analyses (24)(25)(26).…”
Section: Study Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…We still do not have a certain answer on the impact of the extension of lymphadenectomy on survival. Leminsky et al also attempt to find a further correlation between the number of lymph nodes removed, neoadjuvant chemotherapy, and survival [ 4 ]. However, the increased use of the currently optimal therapeutic choice, based on NAC and RC, seems to reduce the importance of the number of lymph nodes removed on survival.…”
mentioning
confidence: 99%